PENGARUH PENERAPAN VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP ECOLITERACY DAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Deasy Rahmawati (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2020)
The purpose of this research was to determine the effect of the application of Value Clarification Technique (VCT) to ecoliteracy and critical thinking skills of elementary school students in learning social study. The method used in this study was a quasi experimental design with non- equivalent control group design, using the two study groups. Subjects in this study were students of class IV Komplek SDN Cijerah Indah, Kecamatan Bandung Kulon Kota Bandung. The experimental group was given the treatment of learning Value Clarification Technique (VCT) and the control group was given conventional learning. The results showed that in general there is a difference between learners ecoliteracy experimental class and control class and critical thinking skills among learners experimental class and control class after each class has been getting treatment that has been set.